(3TQM GdeUGHjMs - (3YHO GddWja Hf YHO GdYRjR Hf Cejf GdOjf Hf aQTJG GdcQeGfj, GdeYQha HGHf edc , (B801 (3g`s
(3ChdgG (B:s
(3HYO GdHSedI ; GdMeO ddg GdPj HUQfG HGdUQGW GdeSJbje hHYO jbhd GdYHO GdVYja eMeO Hf YHO GddWja Gf cJGH GdeUGHjM aj Sff GdgOi cJGH aGNQ dg TQM GdJeS efj HYV ENhGfj Cf dh cGf dg TQM LGeY dahGjO Ydi WQjb GdMd aCLHJ edJeSge eY bdI GdHVGYI hbUhQ GdHGYI (B( (3cPG (B)s
(3BNQgG (B:s
(3HGH bJd Cgd GdQOI hGdSYGjI aj GdaSGO Cj eJYQVGf ddgdGc cCfgeG hbaG aj LQa Lgfe Cj aj WQagG aEPG bJd CMOgeG UGMHg ONdGgG LejYG Yf CHj HcQI Yf GdfHj Udi Gddg Ydjg hSde Cfg bGd (B: " (3EPG GdJbi GdeSdeGf HSjajgeG (B"s
(3aj Chdg agQSIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B4 / 59s
(3eYLe GdeDdajf (B2 / 215s
(3cTa GdXfhf (B2 / 1701s
(3TPQGJ GdPgH (B7 / 342s
Keywords: (3GdMOjK hGdeUWdMs